2015
DOI: 10.1002/ps.4043
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic pheromones as a management technique – dispensers reduce Linepithema humile activity in a commercial vineyard

Abstract: Our results showed that pheromone dispensers can significantly reduce Argentine ant foraging in grapevines if they are positioned appropriately. This technique could potentially reduce the abundance of associated mealybugs and potentially attendant virus vectoring areawide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
(57 reference statements)
2
13
0
Order By: Relevance
“…In particular, their communication allows them respond to changes in the type and abundance of food sources via recruitment systems that amplify and enhance functional responses. From waggle‐dance robots that can stimulate bees to forage (Landgraf et al ., 2018) to manipulations of pheromone communication that have been used successfully to control social insects as pests (Westermann et al ., 2016; Sunamura, 2018), tools are available with great potential to be used to manage social insects. For example, ant pheromones have potential uses as herbivore repellents (Offenberg et al ., 2004), while the use of pheromones to enhance the provision of ESs has not yet been studied.…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%
“…In particular, their communication allows them respond to changes in the type and abundance of food sources via recruitment systems that amplify and enhance functional responses. From waggle‐dance robots that can stimulate bees to forage (Landgraf et al ., 2018) to manipulations of pheromone communication that have been used successfully to control social insects as pests (Westermann et al ., 2016; Sunamura, 2018), tools are available with great potential to be used to manage social insects. For example, ant pheromones have potential uses as herbivore repellents (Offenberg et al ., 2004), while the use of pheromones to enhance the provision of ESs has not yet been studied.…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%
“…For example, in vineyards and citrus orchards, a number of studies have shown that ant presence increases populations of mutualistic aphids and coccids and decreases those of some of their natural enemies (e.g., [50][51][52][53][54][55][56]). As a result, additional research has focused on the control of ant populations in these agroecosystems, either by employing chemical substances (e.g., [57][58][59][60][61][62][63][64]) or distracting tending ants by providing sugary substances (e.g., [21]). The latter method may allow the positive effects of ant presence (see [12]).…”
Section: Introductionmentioning
confidence: 99%
“…Choe et al (2014) evaluated the use of trail pheromones in an attract-and-kill approach, in which the addition of pheromone to insecticides (fipronil and bifenthrin) increased their efficiency, leading to a higher ant mortality due to a higher exposure to toxicants. The effect of trail disruption of hemipteran-tending ants was evaluated in vineyards, determining that the dispensers installed near the base of the grapevines were more efficient, reducing the L. humile traffic in the plants by 73-79% (Westermann et al 2016). Presently, trail disruption has been tested mainly on L. humile among the ant species inhabiting vineyards and the economical sustainability has yet to be evaluated, so that no commercial products have been implemented by manufacturers.…”
Section: Control Of Mealybug-tending Antsmentioning
confidence: 99%